Istota i typologia zespołów zadaniowych - Lichtarski, Janusz Marek (The Nature and Typology of Task Forces, 2008)
There are many kinds of task forces in practice of contemporary organizations, as well as there are significant differences among those teams. At the same time we can observe a lack of typology of task forces in the literature. The goal of the article is to explain the nature of task forces and to present the typology based on eight independent criteria. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 149-158